Experiential Learning Model and Learning Motivation on Descriptive Text Writing Skills - Yulfita; Afnita (LPPM Undiksha, 2024)
This research began with various students' difficulties in maintaining cohesion and coherence when writing descriptive text. In addition, the use of appropriate vocabulary is also a significant problem. Students often use words that are not appropriate to the context or lack variety, so that their writing becomes monotonous and less interesting. These difficulties indicate that there is an urgent need to improve students' descriptive text writing skills through more effective and innovative learning approaches. This research is classified as an experimental type of research using a factorial design. Data was taken from 32 experimental class students and 32 control class students using descriptive text writing skills test instruments and learning motivation questionnaires. The results of the analysis and discussion in this research confirm that the Experiential Learning model is effective in improving descriptive text writing skills for both students with high and low learning motivation, so that the Experiential Learning model and learning motivation do not interact significantly with each other. These findings support the hypothesis that direct experience and critical reflection offered by the Experiential Learning model can enrich the learning process and improve descriptive text writing skills. Thus, it can be concluded that the Experiential Learning model is significantly more effective than conventional methods in improving descriptive text writing skills, regardless of whether students' levels of learning motivation are high or low. The implications of this research indicate that the use of experience-based learning models and increasing learning motivation can significantly improve students' writing skills.